CUSTOMER SATISFACTION IN MOBILE PHONE SERVICES IN BANGLADESH: A SURVEY RESEARCH - Mohammed Belal Uddin; Bilkis Akhter (Management & Marketing)
This study seeks to explore customer satisfaction and its influencing factors of the mobile phone operation industry in Bangladesh. Data were collected through a questionnaire survey form a diversified representative sample. An iterated factor analysis with principal component analysis (PCA) and structural equation modeling (SEM) including measurement model and structural model were applied to analyze data. The empirical results demonstrate that service quality and fair price have indirect influence on customer satisfaction of a mass service industry (i.e., mobile phone operators) through perceive value. Perceived value has mediating role between quality, charge fairness and satisfaction. Furthermore, result shows that fair price has positive direct impact on customer satisfaction, whereas, the results did not find any significant direct impact of service quality on customer satisfaction. Mobile phone operators are recommended to formulate operations and marketing strategies that focus on expectations of customers to enhance level of satisfaction. Similar industries may reveal similar relationship features in respect to these relationship constructs, if they are under similar category.